Consumption Versus Wage Taxation - Helpman, Elhanan; Sadka, Efraim (Quarterly Journal of Economics, 1982)
Elhanan Helpman, Efraim Sadka; Consumption Versus Wage Taxation*, The Quarterly Journal of Economics, Volume 97, Issue 2, 1 May 1982, Pages 363–372, https://doi